Certain features of using modified collagen-containing raw materials with prolonged shelf life in food technology - E. V. Litvinova; E. I. Titov; S. N. Kidyaev; A. Yu. Sokolov; V. L. Lapshina (Теория и практика переработки мяса, 2022)
In the current circumstances, trends in nutrition of a person striving to lead a healthy life-style require intake of meat products with the reduced energy value, minimal amounts of fat, increased protein mass fraction, presence of substances improving homeostasis of the body. The synergism of the modern nutrition science and meat industry enables creating food products that satisfy consumers’ demand. Today, in the Russian Federation, a theoretical and practical base of the technology development has been collected to the full extent in the field of rational processing of secondary raw materials in the food industry, optimal use of animal secondary raw materials, study of the protein ingredients of animal and plant origin and their deep scientifically substantiated processing, improvement of technological processes and equipment, and correspondently, product range extension. The paper broadens the information about the modified collagen-containing raw materials (cattle rumen), examines physico-chemical characteristics of the collagen-containing raw material and its changes in the process of freeze-drying with a special attention paid to the study of changes in the histological structure. The presence of the relatively uniform fibrillar structure was determined, which facilitated discovering the functional potential of proteinoids that form the fibrillar matrix in the composition of products from different groups. Analysis of IR-spectra revealed several significant absorption bands linked with the state of peptide bonds. The character of bands is linked with the complex of valence and deformation vibrations of the N- and С- types. It is believed that IR-spectra reflect conformations in the protein secondary structure, which suggests preserving properties of the tropocollagen particle or collagen molecule. Freeze-dried modified collagen-containing cattle rumen was tested by the example of jellies. The obtained databank broadens information about physico-chemical properties of modified collagen-containing raw materials (cattle rumen).